2017
DOI: 10.1038/srep46684
|View full text |Cite
|
Sign up to set email alerts
|

Live cell imaging of mitochondria following targeted irradiation in situ reveals rapid and highly localized loss of membrane potential

Abstract: The reliance of all cell types on the mitochondrial function for survival makes mitochondria an interesting target when trying to understand their role in the cellular response to ionizing radiation. By harnessing highly focused carbon ions and protons using microbeams, we have performed in situ live cell imaging of the targeted irradiation of individual mitochondria stained with Tetramethyl rhodamine ethyl ester (TMRE), a cationic fluorophore which accumulates electrophoretically in polarized mitochondria. Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 20 publications
(28 reference statements)
0
32
0
2
Order By: Relevance
“…The images were captured with a Zeiss Axio observer Z1 microscope with MetaMorph software (Molecular Devices) at intervals of 600 ms. TMRE was excited at 540-600 nm and emission collected at 585-675 nm. Carbonyl cyanide 4-(trifluoromethoxy) phenylhydrazone (FCCP), which uncouples the oxidative phosphorylation process and depolarizes mitochondria, was used as a positive control (52,53). A maximum of 2 mitochondrial puncta were taken per acinar cell (53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The images were captured with a Zeiss Axio observer Z1 microscope with MetaMorph software (Molecular Devices) at intervals of 600 ms. TMRE was excited at 540-600 nm and emission collected at 585-675 nm. Carbonyl cyanide 4-(trifluoromethoxy) phenylhydrazone (FCCP), which uncouples the oxidative phosphorylation process and depolarizes mitochondria, was used as a positive control (52,53). A maximum of 2 mitochondrial puncta were taken per acinar cell (53).…”
Section: Discussionmentioning
confidence: 99%
“…Carbonyl cyanide 4-(trifluoromethoxy) phenylhydrazone (FCCP), which uncouples the oxidative phosphorylation process and depolarizes mitochondria, was used as a positive control (52,53). A maximum of 2 mitochondrial puncta were taken per acinar cell (53). Trypsinogen activation.…”
Section: Discussionmentioning
confidence: 99%
“…Within this dogma the cytoplasm, the cellular environment in which most cellular processes take place, has rarely been taken into account. With the development of microbeam facilities, the role of the cytoplasm in radiation-induced biological responses became increasingly important in studies of cytoplasm targeted reactions (Walsh et al 2017), bystander cellular responses, (Tartier et al 2007) and in interactions with gold nanoparticles (Ghita et al 2017).…”
Section: Much Of Radiation Biology and Radiotherapy Builds On The Assmentioning
confidence: 99%
“…In particular, the very precise dose delivery has played a fundamental role in the investigation of non-targeted effects where the radiation response is induced in cells which are not directly exposed to ionising radiation . The technology has also recently contributed to the discovery of important novel time-sensitive interaction mechanisms of ionizing radiation with cells and tissues (Ghita et al 2017;Walsh et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Leach et al [70] proposed a mechanism by which IR-induced mtROS and mtRNS trigger mitochondrial Ca 2+ release with subsequent uptake by adjacent mitochondria, which in turn undergo a transient permeability transition with mtROS and mtRNS production and Ca 2+ release, in this way propagating the signal. A recent experiment using carbon ion and proton microbeams demonstrated that energy absorption within a mitochondrial cluster caused a near-instant (< 1 s) and simultaneous depolarization of all the mitochondria belonging to the cluster and of connected mitochondria as far as 18 µm away from the irradiated site [71]. The authors proposed changes in the membrane structure such as lipid peroxidation caused through a direct or indirect (ROS-mediated) action as possible causes of the depolarization.…”
Section: The Physics and Biology Of Radiotherapy Against Cancermentioning
confidence: 99%